1981
DOI: 10.1523/jneurosci.01-10-01142.1981
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gonadectomy, androgen exposure, or a gonadal graft in the neonatal rat on the volume of the sexually dimorphic nucleus of the preoptic area

Abstract: Although the volume of the sexually dimorphic nucleus of the preoptic area (SDN-POA) of the adult rat has been shown to be modified by the hormone environment early in postnatal life, the present study was performed to clarify several fundamental questions related to this process. This study was designed to evaluate the ability of exogenous testosterone propionate (TP), or a gonadal graft, to influence SDN-POA volume in rats which were gonadectomized as neonates. Orchidectomy on day 1 resulted in an approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(70 citation statements)
references
References 14 publications
2
68
0
Order By: Relevance
“…The developing SDN-POA size, like that of the AVPV, is organized by endogenous gonadal steroid hormones [66]. More specifically, testosterone given to fetal rats on gestational days 18, 19 or 20 (but not earlier in gestation) or on postnatal days 2, 3, 4 or 5 resulted in a larger SDN-POA of females (i.e., masculinized; [125,126]), and deprivation of endogenous hormones via neonatal castration (day 1) in male rats caused the SDN-POA to be smaller, suggesting a feminizing or demasculinizing event [81].…”
Section: Sexually Dimorphic Nucleus Of the Preoptic Area (Sdn-poa)mentioning
confidence: 99%
“…The developing SDN-POA size, like that of the AVPV, is organized by endogenous gonadal steroid hormones [66]. More specifically, testosterone given to fetal rats on gestational days 18, 19 or 20 (but not earlier in gestation) or on postnatal days 2, 3, 4 or 5 resulted in a larger SDN-POA of females (i.e., masculinized; [125,126]), and deprivation of endogenous hormones via neonatal castration (day 1) in male rats caused the SDN-POA to be smaller, suggesting a feminizing or demasculinizing event [81].…”
Section: Sexually Dimorphic Nucleus Of the Preoptic Area (Sdn-poa)mentioning
confidence: 99%
“…In the adult rat, the volume of the SDN-POA is determined by the perinatal action of androgens. 21,22,23,30,32 Jacobson et al 31 have found that gonadectomized and adrenalectomized male rats showed a higher percentage of radioactively labeled cells in the SDN-POA following exposure to [ 3 H]testosterone than gonadectomized and adrenalectomized females. 31 This sex difference might be due to a difference in AR levels in the mPOA.…”
Section: Androgen Receptor Immunoreactivitymentioning
confidence: 99%
“…A striking sexual dimorphism in gross morphology of the medial preoptic area (sexually dimorphic nucleus of the preoptic area: SDN-POA) has been recognized in the rat brain 14 . The development of this nucleus starts during late fetal life and depends on the hormonal environment at the critical period of sexual differentiation [14][15][16] . In genetic males, the relatively high levels of perinatal testosterone are aromatized to estradiol in the nervous cells of SDN-POA and the estrogenic signals may be directly responsible for the increase of SDN-POA volume.…”
Section: Development Of the Female Genital Organs And Profile Of Hormmentioning
confidence: 99%